Bad housekeeping ; AIDS ; A comic book of their own [videorecording] - Lazaro, Cheche (The Probe Team, 1995)
A closer book at some questionable expenditures of the Congressional Office ; life from the point of view of people with AIDS ; and the life of a young group of artists finding expression through comic books